Attempt to Increase Public Awareness of Landslide Risks through Recognition of Symptoms and Preventive Measures in Sidoharjo Village, Samigaluh - Tedja Trisnaning, Paramitha; Ani Apriani (ReTII, 2024)
The landslide hazard in Sidoharjo Village is included in the high class with a moderate to high level of vulnerability. This is due to the low capacity of the community in dealing with landslide disasters. A number of local communities lack of understanding of their homes located in landslide-prone areas. In order to minimize the potential risk, landslide early warning system have been installed in a number of places However, it does not cover all landslide-prone areas in Sidoharjo Village. Therefore, this community service aims to increase the effectiveness of mitigation in Sidoharjo Village. Community service is carried out through presentation of material that includes a general explanation of the landlslide symptoms by providing examples and pictures related to symptoms of landslides and landslides prevention activities. Community service were carried out quite effectively, as shown by the enthusiasm of the participants during the delivery of the material which was followed by a discussion. There was an increase in understanding of landslide symptoms and landslide prevention efforts among the Sidoharjo Village government apparatus, as indicated by a sig value <0.05 at a 95% confidence level.